2020
DOI: 10.1109/jsyst.2019.2958829
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Resilient Complex Systems: The Necessary Shift Toward Complexity Science

Abstract: This position article addresses resilience in complex engineering and engineered systems (CES). It offers a synthesis of academic thinking with an empirical analysis of the challenge. This article puts forward argumentations and a conceptual framework in support of a new understanding of CES resilience as the product of continuous learning in between disruptive events. CES are in continuous evolution and with each generation they become more complex as they adapt to their environment. While this evolution take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 55 publications
0
10
0
1
Order By: Relevance
“…Risk analysis modeling, "must evaluate consequences for each risk scenario as functions of the threat (initiating event), the vulnerability and resilience of the system, and the time of the event" [21]. There is a need to "work with the reality that CES often change over time, developing new features, and evolving to meet changes in their operating environment" [1].…”
Section: A Resilience and The Research Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk analysis modeling, "must evaluate consequences for each risk scenario as functions of the threat (initiating event), the vulnerability and resilience of the system, and the time of the event" [21]. There is a need to "work with the reality that CES often change over time, developing new features, and evolving to meet changes in their operating environment" [1].…”
Section: A Resilience and The Research Gapmentioning
confidence: 99%
“…ne key factor in improving the resilience of complex engineered and engineering systems is understanding complex resilience situations, in which there may be multiple threats, interactions, and disruptions. The term complex engineered or engineering systems (CES) [1] includes both: (i) complex systems that are engineered, being the outputs of engineering activitysuch as railway networks, power plants and computers; and (ii) complex systems that carry out engineering, being the capability systems that design, manufacture, operate, supply, maintain, and decommission engineered systemssuch as the organizations that build or maintain rail networks.…”
Section: Introductionmentioning
confidence: 99%
“…The conceptual model in Figure 1 and the systemic narrative that supports it draw upon an extensive literature review of potential systemic approaches to the characterisation of National Infrastructure (Dolan, 2017), a literature review of the application Rinaldi's six interdependency dimensions (Rinaldi et al, 2001) to National Infrastructure (Dolan and Street, 2019) and an extensive body of work on resilience. Dolan, (2017) observed that National Infrastructure can be characterised systemically as a complex adaptive system (Oughton et al, 2018), an interdependent system (Rinaldi et al, 2001); a sociotechnical system (STS); a high-risk (tightly coupled and interactively complex) system (Perrow, 2011); Large Technical Systems (LTS) (Hughes, 1989), an intentional and dynamic built system (Hollnagel, 2014), a complex engineered system (Punzo et al, 2020) or as a network of conversion points (Varga et al, 2014). Based on which, Dolan, (2017) concluded that each approach offers useful insights relevant to developing systemic understanding of the characteristics, performance, resilience and societal value of National Infrastructure.…”
Section: Systemic Characterisation Of National Infrastructurementioning
confidence: 99%
“…Resilience is actually a popular topic in the area of complex science systems [7], [9], such as computer science, ecology, and environmental science. However, these works could not be easily extended to the communication scenario in IIoT, where infrastructure is highly coupled temporally and spatially.…”
Section: Introductionmentioning
confidence: 99%